Boots on the Ground: Means, Ends, and the American Military Commitment to Europe. Issue 4 (18th March 2021) - Schmidt, Sebastian
Abstract: The North Atlantic Treaty Organization and the security commitment it entails are cornerstones of the current international order. Despite this centrality, international relations scholarship is ill equipped to explain the origin of the American commitment to Europe in the form of a long-term, peacetime military presence. At the time, this disposition of military forces represented a historically novel practice. The rational and norm-oriented logics of action that characterize much international relations theory explain cooperation as proceeding from a foundation of given interests. This perspective constrains the ability of analysts to make sense of the dynamic nature and potential creativity of cooperative endeavors. Building on a pragmatist understanding of action, this paper conceptualizes cooperation as a contingent process, characterized by the reciprocal relationship of means and ends, through which actors' initially ambiguous interests become more concrete. The ends of cooperation emerge endogenously, and the potential for creativity is inherent in the process. This dynamic resulted in the specific form of the American commitment to Europe. A pragmatist account foregrounds agency and in doing so draws attention to important developments that traditional analyses may overlook or assume in the effort to reconstruct a pre-existing structure of interests as the basis for cooperation. By underlining the processual cast of action, this paper also helps recontextualize institutionalization as one step within a broader cooperative dynamic.